Potensi Chlorella Sp. untuk Menyisihkan COD dan Nitrat dalam Limbah Cair Tahu - Istirokhatun, Titik; Aulia, Mustika; Utomo, Sudarno (Universitas Diponegoro, 2017)
In order to examine the potential use of tofu-processing wastewater as growth media for microalgae, this research was conducted by cultivating microalgae in varying concentrations. The type of microalga selected in the experiment was Chlorella sp. due to its high reproductive rate. The ability of Chlorella sp. in removing the levels of COD and nitrate contained in the tofu liquid waste were also investigated. This study examined the microalgae growth rate, microalgae cell abundance values, reduced organic levels of COD and nitrate of Chlorella sp which cultivated in tofu wastewater medium. The optimum growth of Chlorella sp was found at 30% v/v of tofu wastewater which reduce COD and nitrate up to 77.40% and 30.03% respectively. From this study, we concluded that tofu-processing wastewater is effective to use as microalgae growth media and at the same time, effective to eliminate COD and nitrate.